2011
DOI: 10.1016/j.chom.2011.06.010
|View full text |Cite
|
Sign up to set email alerts
|

A Tick Mannose-Binding Lectin Inhibitor Interferes with the Vertebrate Complement Cascade to Enhance Transmission of the Lyme Disease Agent

Abstract: Summary The Lyme disease agent, Borrelia burgdorferi, is primarily transmitted to vertebrates by Ixodes ticks. The classical and alternative complement pathways are important in Borrelia eradication by the vertebrate host. We recently identified a tick salivary protein, designated P8 that reduced complement-mediated killing of Borrelia. We now discover that P8 interferes with the human lectin complement cascade resulting in impaired neutrophil phagocytosis and chemotaxis, and diminished Borrelia lysis. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
195
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(198 citation statements)
references
References 31 publications
2
195
1
Order By: Relevance
“…Many studies have identified CTLs as an important family of pattern recognition receptors (PRRs) that are involved in the induction of innate immunity gene expression in response to pathogen invasion in vertebrates (16,19). Response signaling is primed after glycan recognition and binding by CTLs (20)(21)(22)(23)(24). However, during flavivirus infection in mammals and insects, certain CTLs are recruited to facilitate infection.…”
mentioning
confidence: 99%
“…Many studies have identified CTLs as an important family of pattern recognition receptors (PRRs) that are involved in the induction of innate immunity gene expression in response to pathogen invasion in vertebrates (16,19). Response signaling is primed after glycan recognition and binding by CTLs (20)(21)(22)(23)(24). However, during flavivirus infection in mammals and insects, certain CTLs are recruited to facilitate infection.…”
mentioning
confidence: 99%
“…Third, because the borrelia-expressed ligand that interacts with MBL has not been identified and because LB in Europe is caused mainly by B. garinii and B. afzelii, a similar study should be performed in the United States to investigate whether deficient MBL pathway of the complement cascade also is a risk factor in patients in an area in which B. burgdorferi sensu stricto is the only encountered genospecies. However, the study that revealed the essential role of the MBL pathway in the eradication of borrelia was performed with B. burgdorferi sensu stricto, which suggests that similar results would be obtained in the United States (7).…”
Section: Discussionmentioning
confidence: 79%
“…It was recently revealed that the tick salivary lectin pathway inhibitor effectively inhibits the binding of MBL to its ligand at the tick bite site, thereby interfering with complement-mediated killing of borrelia (7,8). This finding highlights the importance of MBLmediated protection against LB.…”
Section: Yme Borreliosis (Lb) Is the Most Common Pathogenic Tick-mentioning
confidence: 90%
“…Proteins of the Salp15-like multigenic family are produced in the tick salivary glands and bind to Borrelia spirochetes to modulate host immunity, thus facilitating infection of the host [13,14]. Tick saliva secreted into the host suppresses local host immune responses, primarily to enable blood acquisition; however, the resulting host immunosuppression facilitates host infection [15-18]. Since tick salivary secretions are the main mediators of host immunosuppression or immunomodulation, salivary composition plays a critical role in tick-borne pathogen transmission and represents a major topic of interest to researchers in the field [3].…”
Section: Ticks Hosts and Pathogensmentioning
confidence: 99%